Dynamics of educational innovation processes through the analysis of social networks (Nexo Revista Científica, 2021)
The subject of educational innovation processes is analyzed, through the Analysis of Social Networks (ARS) in order to determine the edges of the educational innovation processes carried out by teachers of the Systems Engineering career of the National University of Engineering (UNI) with its respective order, in the I Semester of the year 2021. Finding that, "documenting" is the educational innovation process that is least carried out and the one with the most practice is "measurement of results", in addition, the processes that have the opportunity are identified. improvement in future training strategies related to educational innovation in the career.